EXPLORATORY DATA MINING OF SOME PLANT SPECIES AGAINST AEDES AEGYPTI - Rajmohan Devadass; Haldurai Lingaraj; Logankumar Kandhasamy (International Journal of Pharmaceutics and Drug Analysis, 2014)
Biological databases contain a wide variety of data types, often with rich relational structure. On sequence multi-relational data mining techniques frequently are applied to biological data. Extracts of the different plant species were evaluated for the egg hatchability, larvicidal and pupicidal activity of mosquito, Aedes aegypti under the room temperature in the laboratory. Dosage value as expressed in ppm was 10 to 400 for Aedes aegypti. A relationship was observed between the plant extract doses and percentage mortality. The percentage of egg hatchability, larval and pupal mortality was found to be increased with increase in the dosage. Based on the probit analysis, the LC50 value of egg, instars and pupae hence assumed.